Ultrasound : advances in food processing and preservation - Bermúdez-Aguirre, Daniela (Academic Press, an imprint of Elsevier, 2017)
Ultrasound is an emerging technology that has been widely explored in food science and technology since the late 1990s. The book is divided into three main areas.Chapters 1 to 5 focus on the basic principles of ultrasound and how the technology works on microbial cells, enzymes, and the chemistry behind the process. Chapters 6 to 15 cover the application of ultrasound in specific food products and processes, discussing changes on food quality and presenting some innovations in food ingredients and enhancement of unit operations. Finally, Chapters 16 to 20 present some topics about manufacture of ultrasound equipment and simulation of the process, the use of the technology to treat food industry wastewater, and an industry perspective. The laws and regulations concerning emerging technologies, such as ultrasound, are also discussed, including the new Food Safety Modernization Act. Provides a clear and comprehensive panorama of ultrasound technologyContains updated research behind this technologyBrings the current tested product and future usesExplores potential future use within the food industry.--Resumé vydavatele